A review of the determinants of share prices. - Sunde, Tafirenyika; Sanderson, Abel (Science Publications, 2009)
The main purpose of the review was to qualitatively establish the determinants of share prices in Zimbabwe. The review was carried out in 2006 before the situation in Zimbabwe deteriorated to the level where it is at the moment. Approach: To gather the information that we wanted we used interviews and the archival method. We targeted the people in the various organisations/companies that are registered on the Zimbabwe Stock Exchange (ZSE), stock exchange staff, stock broking firms, investment analysts and chief executives. Results: We concluded that there are economic, political and social factors that determine the stock prices in Zimbabwe. However, economic and political factors were established to be the dominant factors in the determination of stock prices. Conclusion: We concluded that if the stock exchange is to perform well the economic and political situation in the country has to be stable. In other words government has to take some deliberate steps to ensure that the economy of the country is well run and also that there is political stability.
Keywords: Stock market - Zimbabwe; Zimbabwe Stock Exchange; ZSE; Zimbabwe - Economic factors; Zimbabwe - Political factors; Zimbabwe - Stability factors